HIROYA KAWAGUCHI, The Essentials of Japanese Patent Law - Heath, Christopher (Zeitschrift für Japanisches Recht, 2009)
HIROYA KAWAGUCHI, The Essentials of Japanese Patent Law Kluwer Law International 2007, xix and 294 p., 122 €.